Digital Technology Literacy as a Mediator between Visionary Leadership and Employee Performance in Local Health Offices: Evidence from West Java, Indonesia - Dadang, Abdulah Mubarok; Disman, Disman; Senen, Syamsul Hadi; Sojanah, Janah; Purnamasari, Imas (Jurnal Manajemen Pelayanan Publik, 2026)
Digital transformation in public services requires adequate digital technology proficiency among employees, yet competency gaps remain a persistent challenge within Indonesian health offices. This study examines the role of digital technology literacy as a mediator between visionary leadership and employee performance. Using a quantitative cross-sectional design, data were collected from 180 managers of the Minimum Service Standard (SPM) program across 27 district and city health offices in West Java, selected through proportional stratified random sampling based on office size. Data were analyzed using SPSS 20 and SmartPLS 4.0 (PLS-SEM). The results show that visionary leadership significantly influences digital technology literacy (β = 0.619, p < 0.001), digital technology literacy significantly and positively influences employee performance (β = 0.570, p < 0.001), and digital technology literacy partially mediates the relationship between visionary leadership and employee performance (β = 0.353, p < 0.001), with a mediation ratio (VAF) of 75.8%. These findings offer theoretical implications through the integration of TAM, Social Cognitive Theory, and Transformational Leadership Theory, as well as practical implications for designing visionary-leadership-based digital literacy programs in the public health sector.